PENGARUH LIKUIDITAS, PROFITABILITAS DAN PPh TERHADAP KEBIJAKAN HUTANG (STUDI KASUS PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2014 – 2018 - Mafatihul Ayunina; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
AbstractThe purpose of this study is (1) to determine the effect of liquidity on debt policy (2) to determine the effect of profitability on debt policy (3) to determine the effect of income tax on debt policy.The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the 2014-2018 period of 45 companies. In this study using a sampling technique with purposive sampling technique to obtain a sample of 15 property and real estate companies. Analysis of the data used in this study using SPSS version 16. For data analysis methods used in this study include normality test, multiple linear regression test, classic assumption test and hypothesis test. The results of this study indicate that liquidity has a significant effect on debt policy, profitability has a significant negative effect on debt policy while income tax have a significant effect on debt policy. Keywords: Liquidity, Profitability, Income Tax and Debt Policy.